Formulasi Sediaan Lip Gel Dari Ekstrak Etanol Kulit Buah Nanas (Ananas comosus (L.) Merr.) Sebagai Pelembab Bibir - Fadhila, Fadhila Abadi Zahra; Indriyanti, Niken; Satriani Badawi (Jurnal Riseta Naturafarm, 2024)
Lips are a facial area that is vulnerable to adverse environmental influences, which can lead to discomfort such as dry, chapped lips, and a dull appearance. Lip gels are commonly used in lip care. Pineapple peel waste (Ananas comosus (L.) Merr.) contains compounds that can be utilized for lip care. The objective of this study was to determine the formulation of a lip gel preparation by testing its physical properties, irritation, and effectiveness as a lip moisturizer. This study is an experimental study. Base optimization was carried out, followed by formulation of preparations with pineapple peel extract concentrations of F1=3%, F2=5%, and F3=7%, physical evaluation of the preparation, namely organoleptic tests, homogeneity tests, spreadability tests, adhesiveness tests, viscosity, pH, irritation tests, and moisturizing effectiveness tests. The results showed that pineapple peel extract can be used as an active ingredient in lip gel preparations. The physical properties of the preparations were semi-solid, yellow to brownish in color with a characteristic pineapple aroma, and did not cause irritation or erythema. All formulas were still within the requirements of good characteristics. The lip gel formulation F2 was more effective based on the results of the percentage increase in moisture content, which was 73.18%.